FITOREMEDIASI TANAMAN ECENG GONDOK (Eichhornia crassipes) PADA VARIASI PARAMETER FOSFAT PADA LIMBAH LAUNDRY - Ai Silmi; Yusriani Sapta Dewi (FT-USNI, 2023)
Today liquid waste is very worrying because it easily mixes with moving water, for example in rivers. The use of detergents on a large scale is a form of environmental pollution originating from residential areas. The level of pollution will be even more dangerous if left too long. The impact that will be felt is the occurrence of pollution which is difficult to overcome and the disruption of the biota ecosystem in the waters and its surroundings. Therefore it is necessary to manage liquid waste, one of which is the phytoremediation system using the water hyacinth plant (Eichhornia crassipes). The purpose of this study was to determine the effect of water hyacinth with a phytoremediation system to reduce levels of phosphate compounds in laundry waste. The method applied is laboratory experimental which is an experiment conducted to be able to see the effect of the variables that are the object of research with a completely randomized design (CRD) for the experiment. The results obtained in this study were a decrease in phosphate levels of 0.607 mg/L (37.7%) at an interval of 12 days. Data analysis used a test of variance (ANOVA) with a significance value of 0.000, which means it is less than the sig value. < α = 0.05 that there is an influence on the variation in treatment time on the phosphate levels contained in household laundry waste.